CicloPedaleiros: processos educativos decorrentes da prática social da cicloentrega - Mecca, Andréia Cordeiro (Universidade Federal de São Carlos, 2022)
The implementation and consolidation of the neoliberal economic model has resulted in a significant precariousness of work in Brazil and the increase of inequalities. The large amount of people living in socioeconomic vulnerability and the struggle to overcome this situation raises alternatives to income generation. These alternatives promoted exploratory practices like the uberization of work, but they contributed to boost other economies as well. The Solidarity Economy Enterprise called CicloPedaleiros sought, through bicycle deliveries, to generate an income for adults who are aside of the labor market, subject to unemployment and informality. This thesis aimed to identify and understand the educational processes arising from the social practice of bicycle delivery in this enterprise. As methodology, we used participatory research, the systematization of observations through field diaries and analysis based on phenomenology, which led to the emergence of three thematic categories: A) "It is good to wear a helmet just to be sure, at right time you’ll be saved", which made explicit dialogical daily relations between the participants, whose attitudes and speeches were, to a great extent, based on educational processes of solidarity, cooperation and care; B) “I gone there to speak and said, I am from CicloPedaleiros solidarity economy enterprise”, which indicates the educational processes related to the participants’ implicated attitude, for example, when they signed partnerships with shopkeepers and other entrepreneurs in the city, made publicity, attended meetings, kept to agreements, showed they knew the history of the actions and the aspects related to the enterprise; and C) “Precariousness is the word of the year”, which deals with the perception and reflection regarding the precarious forms of work in neoliberalism, reorganizing it according to other principles and needs, that is, as something healthy, pleasurable, and creative. We consider that SE, analyzed by means of the CicloPedaleiros, engenders significant educational processes for the elaboration of new repertoires, which may contribute to the construction of more just and egalitarian societies. SE is, therefore, one of the many educational paths to liberation that is occurring in process, inconclusive. Because of that, it is fundamental that this trajectory involves more and more oppressed, organized, and politicized people in the struggle against capitalism; and that none of these experiences is wasted.
CicloPedaleiros: educational processes arising from the structuring of the solidarity economy enterprise
Keywords: Processos educativos; Cicloentrega; Economia Solidária; Educative processes; Bicycle deliveries; Solidarity Economy; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DOS RECURSOS HUMANOS::MERCADO DE TRABALHO; POLITICA DO GOVERNO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO